Synthesis of functionalized graphene/copper oxide (CuO) nanocomposites and their catalytic activity / Norazriena binti Yusoff - Yusoff, Norazriena (2013)
Graphene sheets incorporated with inorganic metal oxides are emerging as a new class of exciting materials. Nanostructured CuO-based materials have been widely investigated because they are inexpensive, non-toxic, and have unique features such as narrow band gap and high solar absorbency. The focus of this research is to fabricate and characterize copper oxide (CuO) nanostructures, functionalized graphene oxide (FGO) and functionalized graphene/copper oxide (FG/CuO) nanocomposite as well as a study of their catalytic activity. Such a study is important in order to predict the suitability of the FG/CuO nanocomposite as a catalyst for the treatment of wastewater contained dyes. Firstly, CuO nanostructures were synthesized using hydrothermal, reflux, ultrasonication and two steps heating process. The as-prepared CuO, which were characterized by Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM) shows that nanorods, nanoflowers and nanofibrils had been formed. It was found that in the presence of hydrogen peroxide and rod-like CuO synthesized by hydrothermal method, the degradation rate of methylene blue (MB) reached up to 87.5 % after irradiation for 10 hours. This is the highest among all the methods due to the highest crystallinity as observed in X-ray diffraction and well organized structure with high capacity of particles that ensure more active surface site for the degradation of MB. Next, GO was fabricated using simplified Hummers’ method, which was silanized with N-(trimethoxysilylpropyl) ethylenediamine triacetic acid (EDTA-silane) in order to form FGO. Finally, FG wrapped CuO particles hybrid materials were synthesized through hydrothermal method. A series of nanocomposites with varying amount of FGO was prepared to study the morphological changes of CuO crystals on the FG sheets and the effects on the catalytic performance. As seen from the FESEM and TEM images, FG sheets had been decorated with aggregation of needle-like CuO with average size of 20 nm. The iv average size of CuO reduced to 15 nm and less than 15 nm with addition of 20 and 30 mg of FGO. The distribution of CuO nanoparticles were also become more uniform as the amount of FGO is increased due to more nucleation sites on the FGO sheets that can be accommodated by Cu2+ ions, simultaneously hindering the agglomeration of nanoparticles. The micro Raman spectrum clearly shows the blue-shift of G peak position from 1600 cm-1 for nanocomposites with 2 mg FGO to 1605 cm-1 and 1608 cm-1 as the amount of FGO was increased to 20 mg and 30 mg, respectively. This result confirms that there is a strong interaction between CuO and FG as the interaction will be stronger in line with the shift towards higher wavenumbers. The catalytic activity of the nanocomposites was also ascending as higher amount of FGO was used. The sample with 2 mg of FGO shows 87.5 % of dye decomposed after 10 hours. While the degradation percentage is 95.08 % and 99.06 % for nanocomposites with 20 mg and 30 mg FGO, respectively. In summary, the mass ratio of FG:CuO and the electronic interaction between them acted as one of the important parameters that control the CuO particle size and catalytic performance, respectively.